On the functions acting on Besov-type and Lizorkin-Triebel-type spaces. Issue 8 (16th November 2020) - Saadi, Mohamed
Abstract: Let f be a real-valued function defined on ℝ. For some restrictions of the parameters p, q, s and τ, if the function f acts on Besov-type space or Lizorkin-Triebel-type space by composition then the composition operator Tf ( f ) = f ᵒ g defined on these spaces is trivial i.e. f is a linear function.